RPG-Based Educational Game for Personal Data Security Awareness in Elementary School Students: A Design and Usability Study - Muhamad Rizal Fahlefi; Uky Yudatama; Dimas Sasongko; Nuryanto Nuryanto; Setiya Nugroho; Purwono Hendradi (Journal of Information Technology and Cyber Security, 2026)
As more and more elementary school-aged children use the internet, they are more likely to be exposed to cybersecurity threats, especially when it comes to keeping their personal information safe. Various educational media have been developed to introduce cybersecurity concepts to children, but most remain passive and do not engage children in simulated real-life digital risk situations. This research addresses this gap by proposing an RPG-based educational game that integrates personal data security concepts into gameplay missions tailored to the cognitive characteristics of children aged 10–12. The goal of this study was to create and assess an educational game that could serve as a substitute learning tool for personal data security. The game was developed using the Game Development Life Cycle framework and implemented using RPG Maker MV. Usability testing involved 20 elementary school students and was carried out through direct observation of 13 game scenes. The success rate indicates the number of students who were able to complete each scene independently. The test results showed that the beginning and end of the game had low success rates, indicating issues with text readability, navigation clarity, and reflective elements. The results showed that iterative improvements in the beta phase improved interface clarity and the gameplay experience. The findings in this study indicate that usability-based improvements have an important role in the design of educational games for children, and RPG-based educational games have the potential to be interactive and contextual personal data security education media.